The Effectiveness of Discovery Learning with Visual Media on Students’ Learning Outcomes in Integrated Primary Science and Social Studies - Ferda Juniarti; Riduan Febriandi; Yuni Krisnawati (Program Studi PGSD Universitas Madako Tolitoli, 2026)
The study was motivated by students’ low academic achievement, with only 26.92% meeting the minimum learning mastery criteria. this research aimed to examine both the differences and the effect of Discovery Learning supported by visual media on the learning outcomes of fourth-grade elementary school students in integrated science and social studies. A quantitative quasi-experimental method employing a nonequivalent control group design was utilized. The participants consisted of 51 fourth-grade students from two classes (IVA and IVB). Data were collected through objective tests administered as pretests and posttests and were analyzed using an independent samples t-test. The findings indicated that the experimental group achieved a higher mean posttest score (76.15) compared to the control group (74.40). The learning mastery rate also increased to 77% in the experimental group, while the control group reached 76%. Hypothesis testing revealed that the calculated t-value (2.13) exceeded the critical t-value (2.010), indicating a statistically significant difference in learning outcomes between students who were taught using Discovery Learning supported by visual media and those who received conventional instruction. Therefore, the implementation of Discovery Learning supported by visual media was found to have a positive effect on improving elementary students’ learning outcomes.